HUBUNGAN TINGKAT PENGETAHUAN TENTANG VULVA HYGINE DENGAN KEBIASAAN PERAWATAN VULVA SAAT MENSTRUASI PADA WANITA USIA SUBUR (WUS) DI DESA WRINGINANOM - Tri Nataliswati; Siti Jannatun Aliya; Sumirah Budi Pertami; Kissa Bahari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Menstruation is a physiological event that occurs in women as a sign of being fertile. Knowledge of vulvar hygiene and vaginal care habits is an important thing that needs to be considered during menstruation by women of childbearing age because they can experience vaginal irritation and itching. The purpose of this study was to analyze the relationship between the level of knowledge about vulvar hygiene and the habit of caring for the vulva during menstruation in Wringinanom Village, Probolinggo Regency. This research method was an analytic survey with a cross sectional design, involving 45 respondents, who celllected with purposive sampling technique. method of data collection with questionnaire techniques and data analysis using rank spearman. The results of this study indicate the level of knowledge of women of childbearing age about vulvar hygiene and vulvar care habits during menstruation, more than half in the sufficient category (60%), there is a significant relationship between the level of knowledge about vulva hygine and vulvar care habits during menstruation in women of childbearing age. women of childbearing age in Wringinanom village (P= 0.02). This study concludes the importance of the influence of knowledge about vulvar hygiene and improving the habits of women of childbearing age with vulvar care during menstruation.